Pedagogical Strategies and Value Internalization in Migrant Education: A Comparative Study of Instructional Frameworks in Indonesia and Malaysia - Ishari, Nurhafid; Wijayanti, Berly; Pramuja, Alvin Dian (CV. Bimbingan Belajar Assyfa, 2026)
Education for migrant children faces unique challenges in balancing academic standards with the internalization of moral and social values, which are crucial for character development. This study analyzes the pedagogical strategies and instructional frameworks implemented in migrant education through a comparative study between Indonesia and Malaysia. Employing a qualitative approach with a comparative research design, this study evaluates instructional practices at Community Learning Centers (PKBM) in Indonesia and Sekolah Binaan (SB) and Non-Formal Education PKBM in Malaysia. The primary findings indicate that differences in curriculum policy and learning environments significantly impact the efficacy of value transfer. While Indonesia emphasizes the integration of religious and civic values, Malaysia focuses more on adapting core competencies for social integration readiness. The results reveal a gap between ideal curriculum design and the reality of instructional implementation on the ground, where the flexibility of teaching methods serves as a determinant for successful value internalization. This study underscores the implication that instructional transformation based on local contextual needs and the adaptation of learning technology are essential to enhance the efficacy of migrant children's education. Therefore, strengthening instructional frameworks that synergize academic competence and character education is an urgency for administrators of migrant educational institutions in both countries to ensure the sustainability of quality education.